Adobe Edge Animate CC for dummies - Rohde, Mike (Hoboken, NJ John Wiley & Sons Inc, 2013)
Learn to create cool animations for the web and mobile devices with Edge Animate. Rohde shows you how to create interactive and animated compositions, and helps you incorporate your creations into web pages or generate files for us with iBooks or InDesign
Introduction -- Getting started with Adobe Edge Animate -- Adopting tools and techniques -- Formatting and animating -- Putting your animation to use -- Creating sample projects -- The part of tens
Includes index
1
Keywords: Cascading style sheets; Computer graphics; HTML (Document markup language); JavaScript (Computer program language); Web site development -- Computer programs; Web sites -- Design